2020
DOI: 10.1038/s41536-020-00101-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided platelet-rich plasma injection and multimodality ultrasound examination of peripheral nerve crush injury

Abstract: Ultrasound-guided platelet-rich plasma (PRP) injection is able to make up for the limitations of applying a single growth factor. The goal of this study was to investigate the effects of serial ultrasound-guided PRP injections of the appropriate concentration on the treatment of sciatic nerve crush injury, and explore the value of multimodality ultrasound techniques in evaluating the prognosis of crushed peripheral nerve. In vitro, optimal concentration of PRP (from 150%, 250%, 450%, and 650%) was screened due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…On the other hand, platelet-rich plasma (PRP) has been reported to have healing effects on tendons, ligaments, muscle, bone, and on the regeneration of peripheral nerves, which have been ascribed to the various GFs it contains 18 , 19 . Although the effects of these GFs on nerve regeneration have been studied 20 , little is known about the biological effects of PRP on Schwann cells (SCs) 17 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, platelet-rich plasma (PRP) has been reported to have healing effects on tendons, ligaments, muscle, bone, and on the regeneration of peripheral nerves, which have been ascribed to the various GFs it contains 18 , 19 . Although the effects of these GFs on nerve regeneration have been studied 20 , little is known about the biological effects of PRP on Schwann cells (SCs) 17 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The medium-term follow-up results from eight RCTs (12 groups) [ 6 , 9 - 12 , 15 , 22 , 23 ] showed greater pain relief with PRP injection compared with the control interventions (MD, 1.00 cm; 95% CI, 0.35–1.65; I 2 =93%, p=0.002) ( Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…PRP has anti-nociceptive [ 5 ], anti-inflammatory [ 6 ], and regenerative properties [ 7 ]. Recent studies have demonstrated the use of PRP in many kinds of pathologies, from fracture-healing [ 8 ] to nerve repair [ 9 ]. Some trials have reported the superiority of PRP for pain-relief and tissue healing compared with other interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we conducted our electrophysiological analysis via a bipolar stimulation electrode. As reported previously ( Rodríguez Sánchez et al, 2019 ; Zhu et al, 2020 ), one electrode was positioned at the proximal and distal end of the sciatic nerve for electricity transduction. Another electrode, was inserted in the belly of the gastrocnemius muscle to record the NCV and DCMAP.…”
Section: Methodsmentioning
confidence: 99%